A Real-Time PCR Assay for the Quantification of Plasmopara viticola Oospores in Grapevine Leaves - Si Ammour, Melissa; Bove, Federica; Toffolatti, Silvia Laura; Rossi, Vittorio (Frontiers in Plant Science, 2020)
Grapevine downy mildew caused by Plasmopara viticola is one of the most important diseases in vineyards. Oospores that overwinter in the leaf litter above the soil are the sole source of inoculum for primary infections of P. viticola; in addition to triggering the first infections in the season, the oospores in leaf litter also contribute to disease development during the season. In the current study, a quantitative polymerase chain reaction (qPCR) method that was previously developed to detect P. viticola DNA in fresh grapevine leaves was assessed for its ability to quantify P. viticola oospores in diseased, senescent grapevine leaves. The qPCR assay was specific to P. viticola and sensitive to decreasing amounts of both genomic DNA and numbers of P. viticola oospores used to generate qPCR standard curves. When the qPCR assay was compared to microscope counts of oospores in leaves with different levels of P. viticola infestation, a strong linear relationship (R2 = 0.70) was obtained between the numbers of P. viticola oospores per gram of leaves as determined by qPCR vs. microscopic observation. Unlike microscopic observation, the qPCR assay was able to detect significant differences between leaf samples with a low level of oospore infestation (25% infested leaves and 75% non-infested leaves) vs. samples without infestation, and this ability was not influenced by the weight of the leaf sample. The results indicate that the qPCR method is sensitive and provides reliable estimates of the number of P. viticola oospores in grapevine leaves. Additional research is needed to determine whether the qPCR method is useful for quantifying P. viticola oospores in grapevine leaf litter.